The Use of Gamification in Teaching Vocabulary of 11th Grade Students at SMAN 4 Mataram - Aisyah, Baiq; Muhaimi, Lalu; Arafiq (Program Studi Pendidikan Bahasa Inggris, 2024)
This study delves into the transformative potential of integrating gamification principles into vocabulary learning for 11th-grade students at SMAN 4 Mataram. Vocabulary acquisition is critical for academic progress, especially in preparation for standardized exams and college admissions, yet conventional methods often lack student engagement. Gamification, defined as the incorporation of game elements into non-gaming contexts, emerges as a promising strategy. The research explores how English teachers at SMAN 4 Mataram employ gamification, addressing questions about the types used, advantages gained, and obstacles faced. Using a qualitative descriptive approach, the study identifies two principal gamification classifications: content gamification, involving modifications to educational materials, and structural gamification, integrating game elements without altering content. Teachers utilize diverse gamification methodologies, fostering interactive learning environments. Challenges include accommodating diverse student abilities and aligning with evolving curriculum requirements. Theoretical implications span educational gamification, cognitive processes in vocabulary acquisition, and motivation theories. Practically, the study aims to enhance students' vocabulary skills, academic performance, and engagement, offering valuable insights for educators and policymakers in leveraging gamification for improved language learning outcomes.